Brother, sister, me and you - Quattlebaum, Mary (National Geographic kids., 2019)
Little ones will delight in the similarities lion, turtle, and even bee siblings have with human brothers and sisters in this charming read-aloud book. It opens with 10 kinds of animal siblings and segues naturally into young human brothers and sisters. The children reprise the animal actions, from leaping and pouncing to splashing and bouncing, and finally snuggling down to sleep. Interesting facts about each featured animal are provided for further learning.